A unique key sharing protocol among three users using non-commutative group for electronic health record system. (17th November 2019) - Misra, Manoj Kumar; Chaturvedi, Atul; Tripathi, S. P.; Shukla, Varun
Abstract: We know that the importance, need and utility of EHR (Electronic Health Record) system is increasing rapidly in the modern world. The developed countries like USA, Canada has adopted this system years ago but still they are facing security issues in that system. The situation is very poor for developing countries like India where data breaching news are very common in EHR system. One can imagine the situation that Indian government is accepting data breaching cases with associated authentication problems and helpless to develop secure EHR system. EHR information is very sensitive and communication over insecure wireless communication channels increases the vulnerability. Here we are going to propose an authenticated key agreement protocol among three users (doctor, hospital and patient) using conjugacy search problem (CSP) and braid decomposition problem (BDP). We discuss the required security analysis of the protocol and prove that the proposed protocol passes the security parameters assuming that the BDP and CSP are hard in braid groups.